Εργασία ενοποιημένου σχεδιασμού : σύστημα ελέγχου εισόδου/εξόδου βηματικών ασθενών με τη χρήση τεχνολογίας RFID στην καρδιολογική εντατική μονάδα Γενικού Νοσοκομείου Λευκωσίας - Ιταλού, Χαρίκλεια; Βασιλείου, Νεόφυτος; Πιερή, Λάουρα (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
At first by this consolidated design project we refer to the continual need to watch specific biosignals of the step wised heart patients from the intensive care unit (cardiology department) at general hospital at Nicosia, through a telemetry system.In addition, there is a strong need to assure that step wised patients are in the intersive unit at any time.Our group-target to satisfy this basic need of the intensive cardiology unit, as the head-master at this unit at the general hospital at Nicosia, Dr Evagoras Nikolaides, asked us.Step wised patients could move anywhere, where’s the unit exist, even in toilets.If for any reason they will try to get out of the intensive unit, the staff at the unit have to know about it at once, with the help of an acoustic signal or optical signal and they have to act at one for the patient’s recovery.In this case at a patient’s entering in a toilet, must be a different acoustic signal and the staff must know about it.The target at our consolidated design project is to decrease the possibility of mortality at the patients at the cardiology intensive unit.In an emergency case, the medical or paramedical staff has three crucial minutes to find the patient and act at once.The only way to find the step wised patients at once, is the help of RFID technology and telemetry system.By this project we try to explain the theoretical basement of the RFID system and the existed telemetry system at the hospital.Then we show the results of this experimental procedure and insist that the RFID technology doesn’t interpolates jam to the telemetry system or any other equipment which are used to the hospital at Nicosia, especially at the intensive unit.There is a simulation at the system in the user’s friendly environment which is coded in the programming language MATLAB.After the extraction of the necessary conclusions, at the end there is a summary brief report that could be done for the improvements on this project.
Keywords: Radio Frequency Identification; Telemetry system; Intensive care unit; Cardiovascular system; Ταυτοποίηση ραδιοσυχνοτήτων; Σύστημα τηλεμετρίας; Εντατική μονάδα; Καρδιαγγειακό σύστημα